Impact of joint status on contraction steadiness of m. quadriceps femoris in people with severe haemophilia. (25th August 2014) - Brunner, A.; Stäuber, F.; Göhler, S.; Czepa, D.; Wendel, M.; Seuser, A.; Hilberg, T.
Summary Impaired contraction steadiness of lower limb muscles affects functional performance and may increase injury risk. We hypothesize that haemophilic arthropathy of the knee and the strength status of quadriceps are relevant factors which compromise a steady contraction. This study addresses the questions if impaired steadiness of the quadriceps is verifiable in people with haemophilia (PWH) and whether a connection between the status of the knee joint and quadriceps strength exists. A total of 157 PWH and 85 controls (C) performed a strength test with a knee extensor device to evaluate their bilateral and unilateral maximal quadriceps strength and steadiness. Isometric steadiness was measured by the coefficient of variation of maximum peak torque (CV‐MVIC in %). For classification of the knee joint status the World Federation of Haemophilia (WFH) score was used. Lower steadiness (higher CV values) was found in PWH compared with C during bilateral [PWH vs. C; 0.63 (0.36/1.13) vs. 0.35 (0.15/0.72), median (Q25/Q75) P < 0.001] and unilateral trials [left leg: 0.70 (0.32/1.64) vs. 0.50 (0.23/1.04), P < 0.05; right leg: 0.68 (0.29/1.51) vs. 0.39 (0.18/0.68), P < 0.001]. PWH with a WFH score difference (≥1) between their extremities showed a less steady contraction in the more affected extremity (P < 0.05). More unsteady contractions have also been found in extremities with lower quadriceps strength compared with the contralateral stronger extremities (P < 0.001), whereby the weaker extremities were associated with a worse joint status (P < 0.001). The results of this study verify an impaired ability to realize a steady contraction of quadriceps in PWH and the influence of joint damage and strength on its manifestation.